(untitled) (GESTIÓN Y TENDENCIAS, 2019)
This article summarizes the objectives pursued by the Labor Reform for the system of labor relations, its rationale and most significant proposals, as well as the great polarization it aroused shortly into its passage through the legislature. The confrontation and mistrust between social actors, diagnosed as a problem that compromises the country’s development path, ultimately contaminated its discussion and legislative passage. Even so, it is hoped that the merits of some of the new rules will serve the purpose of improving the quality of bargaining and strengthening unionization.